Female Representation in Han Characters Containing the Radical 女 (nǚ): A Corpus-Based Critical Discourse Analysis of Ideological Construction and Gender Bias - Noviana Laurencia Surjadjaja; Syihabuddin; Rinaldi Supriadi; Joni Soleman Nalenan; Mohammad Ali (Mandarinable: Journal of Chinese Studies, 2026)
Han characters (汉字) constitute one of the oldest continuously used logographic writing systems in the world, and as such they encode millennia of accumulated cultural values, social hierarchies, and ideological assumptions. This study empirically investigates the representation of women through Han characters containing the radical 女 (nǚ, ‘woman’) by employing a cultural-linguistic framework integrating corpus-based quantitative analysis, semiotic deconstruction, and critical discourse analysis. The research corpus comprises 214 characters drawn from the Kangxi Dictionary (康熙字典) and the Contemporary Chinese Dictionary (现代汉语词典, 7th edition, 2016); a supplementary diachronic corpus of 50 characters with documented oracle bone forms was drawn from the Xiaoxuetang Database of Ancient Chinese Scripts (小學堂). Frequency analysis was conducted against the MARKUS corpus (45 classical texts spanning the Han through Qing dynasties, totaling approximately 2.3 million characters). Results indicate that of the 214 characters analyzed, 61.2% carry connotations that subordinate, restrict, or pathologize the feminine; 22.4% are semantically neutral-descriptive; and only 16.4% bear positive connotations. These findings confirm that the Han writing system functions as an ideological apparatus that reproduces and consolidates patriarchal norms embedded in pre-modern and contemporary Chinese society. The study has implications for language pedagogy in the Indonesian context of Chinese-language education, for script reform policy, and for the broader scholarly debate on writing systems as ideological apparatus.